Hydropower resettlement and livelihood adaptation: the Nam Mang 3 Project in Laos - Sayatham, M.; Suhardiman, Diana (Elsevier, 2015)
Mekong hydropower is developing rapidly. Laos is at the forefront of this development. While hydropower development supports the country’s economic growth, many observers have highlighted the potential negative impacts for people’s livelihoods. Taking the Nam Mang 3 hydropower project as a case study, we examine the impacts of hydropower development on farming households of differing livelihood assets and resources, and how they have responded to these impacts. Linking livelihood asset substitution with livelihood outcomes, we examine factors constraining livelihood adaptation and how these shape rural households’ strategies to cope with socioeconomic and environmental impacts from hydropower development. We conclude that while asset substitution generally can improve people’s livelihoods, access to land continues to play an important role in the process of livelihood reconstruction and the shaping of livelihood outcomes.